Smoking and coronary artery disease risk in patients with diabetes: A Mendelian randomization study - Songzan Chen; Songzan Chen; Fangkun Yang; Tian Xu; Tian Xu; Yao Wang; Yao Wang; Kaijie Zhang; Kaijie Zhang; Guosheng Fu; Guosheng Fu; Wenbin Zhang; et al. (Frontiers in Immunology, 2023)
BackgroundPrevious observational studies have shown an association between smoking and coronary artery disease (CAD) in patients with diabetes. Whether this association reflects causality remains unestablished. This study aimed to explore the causal effect of smoking on CAD in patients with diabetes.MethodsGenetic signatures for smoking were extracted from a large genome-wide association study (GWAS), consisted of up to 1.2 million participants. Four smoking phenotypes were included: smoking initiation, cigarettes per day, age at initiation of regular smoking, and smoking cessation. Genetic associations with CAD in patients with diabetes were extracted from another GWAS, which included 15,666 participants (3,968 CAD cases and 11,696 controls). The analyses were performed using the univariable and multivariable Mendelian randomization (MR) method.ResultsMR analysis revealed that smoking initiation was positively related to CAD risk in patients with diabetes (OR = 1.322, 95% CI = 1.114 – 1.568, P = 0.001), but this association was attenuated when adjusted for cardiovascular risk factors (OR = 1.212, 95% CI = 1.008 – 1.457, P = 0.041). Age at initiation of regular smoking was negatively related to CAD in patients with diabetes (OR = 0.214, 95% CI = 0.070 – 0.656, P = 0.007), but this association became insignificant when adjusted for cardiovascular risk factors.ConclusionsThis study supported the effect of smoking initiation on the risk of CAD in patients with diabetes.